Company’s value added and its intellectual capital coherence - Mačerinskienė, Irena; Survilaitė, Simona (Business: Theory and Practice, 2011)
The importance of small and medium-sized business companies has always been indisputable. Governments are trying to facilitate the entrance into a marketplace; the activity itself and managers are able to administer their companies in their best manner. Despite these facts, the changing environment has made a strong impact on all companies all over the world. In addition to this, nowadays it is not enough just to have a sack of tangible assets in order to have huge company’s value added. The modern century of new technologies, the importance of knowledge and information brought a new attitude to the company. The value added, which is created by the company, depends not only on tangible assets but also on intangible assets, which, by the way, are among the most important in a new modern company. Intellectual capital is intangible, hardly measurable, but plays a vital role in every company’s value added. This paper is aimed at analysing this company’s value added and its intellectual capital coherence, and the model of new company’s value added and its intellectual capital coherence is proposed.